Quantitative study of vimentin gene methylation in stool samples for colorectal cancer screening - Behfar Pakbaz; Raheleh Jabinin; Narjes Soltani; Hossein Ayatollahi; Mohammad Reza Farzanehfar (Wolters Kluwer Medknow Publications, 2019)
Due to importance of screening for colorectal cancer the present study was conducted and aimed at investigating the quantitative methylation of vimentin gene in stool, tumor tissue, and healthy tissue of patients with colorectal cancer (CRC) in comparison with healthy individuals. This is a case-control study in which we measures methylation of the vimentin in tumoral tissue, normal tissue and stool specimens were collected from forty-nine CRC patients as case group and stool and normal tissue specimens were collected from thirty healthy individuals as control group. There was no statistically significant difference in methylation of vimentin in normal tissue (P > 0.05) between the two groups. Moreover, the status of methylated or unmethylated vimentin gene in tumor and stool tissues in the case group was not significantly correlated with their mean age and sex (P > 0.05). This study showed that the specificity and sensitivity of vimentin methylation in stool of CRC patients are 100% and 60%, respectively. Furthermore, the methylation of vimentin in stool of CRC patients has a high-positive predictive value (100%). The results of this study suggested that methylation of the vimentin gene in the stool can be used as a specific marker for the detection and screening of CRC.